2019
DOI: 10.1038/s41598-019-40525-6
|View full text |Cite
|
Sign up to set email alerts
|

A Mycobacterium tuberculosis Beijing strain persists at high rates and extends its geographic boundaries 20 years after importation

Abstract: Transmission of Beijing Mycobacterium tuberculosis can be investigated based on genotypic analysis of clinical isolates. A Beijing strain began to spread on Gran Canaria Island, Spain, at the end of the last century. In 1996, only 3 years after its importation to the island, its frequency had increased to 27.1% of all the isolates. The strain was tracked during the following years, and the most recent data obtained corresponded to 2007-8, when its presence continued to be alarming (21%). In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Impressively, this Beijing pattern2 cluster, the largest Beijing cluster identified in our study, accumulates 13 cases coming from five different East European countries and identified in 6 different regions. In addition to detecting foreign MDR-TB, our study supports the need for a more discriminative tool for Beijing isolates, which is in agreement with other studies that remark that MIRU-VNTR is not the most appropriate technique in this lineage 18 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Impressively, this Beijing pattern2 cluster, the largest Beijing cluster identified in our study, accumulates 13 cases coming from five different East European countries and identified in 6 different regions. In addition to detecting foreign MDR-TB, our study supports the need for a more discriminative tool for Beijing isolates, which is in agreement with other studies that remark that MIRU-VNTR is not the most appropriate technique in this lineage 18 .…”
Section: Discussionsupporting
confidence: 91%
“…Spain has incorporated this technology since 2018, combining with MIRU-VNTR to enable comparison with the previous obtained data. The global use of WGS will provide the possibility of developing other rapid methods, such us allele-specific oligonucleotide PCR, used in other studies to detect specific transmitted strains in subsequent years 18 . According to the criteria fixed for our study, a single isolation of each case of MDR-TB was realized.…”
Section: Discussionmentioning
confidence: 99%
“…Our first interpretation of the results was that the high presence of Beijing A strains was due to an uncontrolled recent transmission major event in Colon. Several studies have described the Beijing lineage as responsible for major outbreaks (Bifani et al., 2002; Iwamoto et al., 2012; Johnson et al., 2006; Perez‐Lago et al., 2019). Colon has elevated rates of poverty, overcrowded and substandard quality housing, and high HIV coinfection, all factors associated with active MTB transmission.…”
Section: Discussionmentioning
confidence: 99%
“…We propose a shortcut based on tailoring strain-specific PCRs, targeting multiple marker SNPs for the strain to be surveyed taken from the WGS data. In previous studies, we demonstrated the efficiency and versatility of this novel approach for optimizing surveillance of actively transmitted strains 1,16 , fast-tracking secondary cases after importation of XDR-TB 17 , determining the presence and/or prevalence of an outbreak strain in a population by analyzing large collections in remarkable short periods of time [18][19][20] , and differentiating between recent transmission and importation in clusters involving migrants 4 . Additionally, this strategy has a potential clinical usefulness when tracking resistant strains, as it would allow us to assume the resistance profile of the tracked strain for a new case infected with it, without the need of characterizing specifically the resistance mutations 1,19 .…”
Section: Discussionmentioning
confidence: 99%